Photochemical and bioactivity examination of fractionated saluang belum root extract (Lavanga sarmentosa) on in-vitro human sperm motility - Silvani Permatasari; Syarpin; Dwi Ari Pujianto (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Saluang belum (Lavanga sarmentosa) is one of Kalimantan's typical plants, which is as efficacious as a traditional medicine to increase sexual activity and male fertility. Based on previous studies, the content of flavonoid and steroid in 70% ethanol extract of L. sarmentosa were able to affect sperm quality of mice. Studies related to L. sarmentosa are still limited for phytochemical test and their bioactivity on human spermatozoa motility in vitro.Objective: This study is to perform phytochemical tests of compound content in fractionation with eluents of high and low polarity, namely methanol and chloroform, and then to test their bioactivity on the motility of human spermatozoa in vitro.Methods: L. sarmentosa was extracted with 96% ethanol and fractionated by using a vacuum chromatography column with chloroform and methanol as the eluent. Then obtained samples were analysed by a quantitative phytochemical test. The samples used in-vitro human spermatozoa were divided into eleven groups: control group, group administered with L. sarmentosa extract eluent chloroform of 10, 50, 100, 500, and 1000 ng/mL, and same concentration with extract eluent methanol. Furthermore, the sperm motility was analysed by using a Computer Assisted Sperm Analyser (CASA). Results: The methanol and chloroform fraction of L. sarmentosa root extract contained metabolites, namely terpenoids, flavonoids, steroids, alkaloids, saponins, and tannins. The sperm motility increased significantly at the treatment group of the methanol and chloroform fractions compared to the control group. There was a significant difference between the sperm motility incubated with methanol and that with chloroform fraction at concentration 500 and 1000 ng/mL.Conclusion: The results of sperm motility were higher in the methanol fraction than those in the chloroform fraction.